Biodegradable dunks to control culicine larvae - R.K. Anish; Bhaskaran Ravi Latha; R. Palani Dorai (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Acorus calamus (Sweet cane) powder was incorporated into a dunk made of a suitable natural binder. Dunks were prepared from neem leaf powder and neem chips (Azhadirachta indica). The efficacies of different concentrations of the preparations on juvenile stages of culicine mosquitoes were evaluated in the laboratory. It was observed that a mortality of 95% were obtained with 2.5% of Acorus calamus dunk within 24 hours. No further development was observed in the remaining 5% of larvae. Similar levels of mortality were obtained with neem leaf dunk and neem chip dunk only after 72 hours.